The 13th Nordic-Baltic Conference of German Scholars 2024, Vilnius University, Abstracts - Bäcker, Iris; Daunorienė, Justina; Plaušinaitytė, Lina; Žeimantienė, Vaiva (Vilnius University Proceedings, 2024)
The abstract book contains the abstracts of the papers presented at the 13th Nordic-Baltic Conference of German Scholars (NBGT2024) from 12 to 14 June 2024 at Vilnius University. The subject-specific focus is on questions of German linguistics, literature and cultural studies as well as the didactics of German as a foreign language. Furthermore, the contributions reflect current political discussions on the status of German in the region. The 63 abstracts are presented in alphabetical order according to the authors' surnames.
Keywords: Nordic-Baltic Conference of German Scholars; German Studies; German as a Foreign Language; Baltic States; Scandinavia; Language Policy